Optimalisasi Boraks Sebagai Bahan Pelapis Tahan Api Pada Kayu Lapis - Fadilah Rizky Damayanti; Mochammad Alfiansyah Putra Sanjaya; Robie Kuncoro; Denny Oktavina Radianto (KOLONI, 2024)
The increasing number of Indonesia's population is certainly in line with the increasing number of housing demand. The need for housing makes the innovation of building materials grow. One of the building materials that is often used is plywood. The use of wood base material as a building material certainly needs to be considered. The number of fires that reached 382 in DKI Jakarta Province in 2022 is one of the factors that make the use of plywood necessary to be considered. Therefore, researchers make innovations by utilizing borax or sodium tetraborate as a fire retardant material to coat plywood. The research method used is in the form of experiments using data from journals and the internet. Data processing in the form of descriptive data results compared to materials used daily.